Reassessing the Influence of Mental Intangibility on Consumer Decision-making. (July 2017) - Rizomyliotis, Ioannis; Konstantoulaki, Kleopatra; Kostopoulos, Giannis; Poulis, Athanasios
This paper explores the influence of mental intangibility on the size of the consideration set, for both tangible products and services. The research also examines the moderating effect of purchase involvement and objective knowledge on the set. Two experimental studies were conducted to examine these relations. Overall, the results indicate that mental intangibility positively influences the size of the consideration set, regardless of the offering type (product or service). This effect is stronger in low levels of knowledge. Consumer involvement does not seem to have a moderating effect on this relation. The studies' implications and recommendations for future research are also discussed.